A narrative review of the impact of work hours and insufficient rest on job performance. Issue 4 (18th February 2023) - Steffey, Michele A.; Risselada, Marije; Scharf, Valery F.; Buote, Nicole J.; Zamprogno, Helia; Winter, Alexandra L.; Griffon, Dominique
Abstract: Objective: This review discusses the scientific evidence regarding effects of insufficient rest on clinical performance and house officer training programs, the associations of clinical duty scheduling with insufficient rest, and the implications for risk management. Study design: Narrative review. Methods: Several literature searches using broad terms such as "sleep deprivation, " "veterinary, " "physician, " and "surgeon" were performed using PubMed and Google scholar. Results: Sleep deprivation and insufficient rest have clear and deleterious effects on job performance, which in healthcare occupations impacts patient safety and practice function. The unique requirements of a career in veterinary surgery, which may include on‐call shifts and overnight work, can lead to distinct sleep challenges and chronic insufficient rest with resultant serious but often poorly recognized impacts. These effects negatively impact practices, teams, surgeons, and patients. The self‐assessment of fatigue and performance effect is demonstrably untrustworthy, reinforcing the need for institution‐level protections. While the issues are complex and there is no one‐size‐fits‐all approach, duty hour or workload restrictions may be an important first step in addressing these issues within veterinary surgery, as it has been in human medicine. Conclusion: Systematic re‐examination of cultural expectations and practice logistics are needed if improvement in working hours, clinician well‐being, productivity, and patient safety are to occur. Clinical significance (or Impact): A more comprehensive understanding of the magnitude and consequence of sleep‐related impairment better enables surgeons and hospital management to address systemic challenges in veterinary practice and training programs.